Applications of ZnO Nanowires as Electrode Materials in Photosynthetic Bio-Photoelectrochemical Cells. Issue 1772 (2015) - Yaghoubi, Houman; Santhanakrishn, Anand Kumar; Khan, Md; Beatty, J. Thomas; Takshi, Arash
ABSTRACT: Harvesting solar energy, is only one of the incentives of incorporating photosynthetic proteins in electrochemical devices. Understanding the interface of photosynthetic protein complexes and organicunderlying electrodes can give rise to development of new generation of nano-bioelectronics for other applications such as sensing, as well. Previous approaches in fabricating photosynthetic bio-hybrid electrochemical solar cells were mainly based on metallic electrodes with protein complexes attached, either directly or through linker molecules. Due to the energy band structure in semiconductors, they potentially can be useful for selective charge transfer in an electrochemical device. In the current study, a two terminal sealed bio-hybrid solar cell device was fabricated comprising of hydrothermally grown ZnO nanowires on fluorine doped tin oxide (FTO) glass working electrode, a Pt counter electrode, and methyl viologen (MV) as a single diffusible redox mediator. The ZnO working electrode was initially characterized using scanning electron microscopy (XRD) and X-ray diffraction (XRD). A solution of dimeric Rhodobacter sphaeroides – light harvesting 1 (RC-LH1) core complexes and redox electrolyte was injected into the cavity between working and counter electrodes. Such structure resulted in ∼0.64 µA.cm -2 photocurrent density and ∼0.24 V open circuit potential difference in the dark and under illumination. Additionally, the device stability tests demonstrated that the current response of such devices remained unchanged after 33 hours storage in the dark.